Synthesis and functionalisation of nanomaterials for biomedical diagnostic applications - McCarthy, Sarah (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
This thesis explores synthesis and functionalisation of a variety of nanomaterials for the purpose of biological detection with a potential focus on medical diagnostics. Early diagnosis is the key to disease prevention, improves patient outcome and reduces the need for aggressive therapies for diseases such as cancer. Therefore we aim to push the boundaries of current detection systems and create new materials for more sophisticated, targeted applications. Using visible detection, magnetic sample recovery, and flow detection systems we hope to create fast, cheap, non invasive detection technologies. This should improve patient compliance, increase voluntary testing and reduce the incidence of advanced stages of disease in the population. Thus, the main goal of this work is to develop new magnetic or multimodal magnetic/plasmonic/fluorescent nanomaterials of various shapes by various synthetic strategies for biomedical applications, in particular for new, improved medical diagnostic techniques, and the detection of biomarkers for disease at early stages.
Embargo End Date: 2020-04-01
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin, 2014